Ulasan Etnobotani Rubroshorea balangeran (Korth) P. S. Ashton & J. Heck. (Dipterocarpaceae) oleh Masyarakat Kalimantan - Letus Sepsamli; Fitria Cita Dirna; Shafira Hanindita; Imam Hidayat (Pro-Life, 2024)
Balangeran is an endemic species of Kalimantan and offers numerous benefits for daily life. Balangeran is one such species utilized by the people of Kalimantan for various purposes. This study was conducted using a literature review method, analyzing various articles, proceedings, and books on the ethnobotanical aspects of Balangeran by comparing similarities and differences and subsequently drawing conclusions from the research. Several aspects collected include taxonomy, ecology and distribution, local names, and ethnobotany. Communities across various provinces in Kalimantan use the Balangeran trunk as building material, the bark as a dye, and make traditional medicines from the bark, leaves, branches, and twigs. Some phytochemical compounds found in Balangeran include alkaloids, saponins, tannins, phenolics, flavonoids, triterpenoids, glycosides, and steroids. However, despite its benefits, the population of Balangeran in the wild is declining and becomes a concern to preserve its existence and benefits through various conservation efforts.